PECTIN METHYLESTERASE INHIBITOR6 Promotes Arabidopsis Mucilage Release by Limiting Methylesterification of Homogalacturonan in Seed Coat Epidermal Cells([C])([W]) - Saez-Aguayo, Susana (American Society of Plant Biologists, 2013)
Imbibed seeds of the Arabidopsis thaliana accession Djarly are affected in mucilage release from seed coat epidermal cells. The impaired locus was identified as a pectin methylesterase inhibitor gene, PECTIN METHYLESTERASE INHIBITOR6 (PMEI6), specifically expressed in seed coat epidermal cells at the time when mucilage polysaccharides are accumulated. This spatio-temporal regulation appears to be modulated by GLABRA2 and LEUNIG HOMOLOG/MUCILAGE MODIFIED1, as expression of PMEI6 is reduced in mutants of these transcription regulators. In pmei6, mucilage release was delayed and outer cell walls of epidermal cells did not fragment. Pectin methylesterases (PMEs) demethylate homogalacturonan (HG), and the majority of HG found in wild-type mucilage was in fact derived from outer cell wall fragments. This correlated with the absence of methylesterified HG labeling in pmei6, whereas transgenic plants expressing the PMEI6 coding sequence under the control of the 35S promoter had increased labeling of cell wall fragments. Activity tests on seeds from pmei6 and 35S:PMEI6 transgenic plants showed that PMEI6 inhibits endogenous PME activities, in agreement with reduced overall methylesterification of mucilage fractions and demucilaged seeds. Another regulator of PME activity in seed coat epidermal cells, the subtilisin-like Ser protease SBT1.7, acts on different PMEs, as a pmei6 sbt1.7 mutant showed an additive phenotype.